2011
DOI: 10.5194/acp-11-9911-2011
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation properties of volcanic ash from Eyjafjallajökull

Abstract: Abstract. The ice nucleation ability of volcanic ash particles collected close to the Icelandic volcano Eyjafjallajökull during its eruptions in April and May 2010 is investigated experimentally, in the immersion and deposition modes, and applied to atmospheric conditions by comparison with airborne measurements and microphysical model calculations. The number of ash particles which are active as ice nuclei (IN) is strongly temperature dependent, with a very small minority being active in the immersion mode at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
97
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 39 publications
10
97
1
1
Order By: Relevance
“…Unlike field measurements, however, it has been suggested that all volcanic ash may have similar ice nucleation efficacy, initiating ice formation in a relatively narrow temperature range of approximately 250 to 260 K (Durant et al, 2008); however, these works are difficult to interpret quantitatively, especially in cases where the nucleation mode is unclear, frozen fractions are unavailable, or the available surface area has not been quantified. More recently, several studies have investigated the deposition-and/or immersion-mode ice nucleation properties of ash from the 2010 eruption of the Eyjafjallajökull volcano in Iceland (Steinke et al, 2011;Hoyle et al, 2011;Bingemer et al, 2012). The results of these studies, combined with previous studies on large, 250-300 µm ash particles from the 1980 Mt.…”
Section: G P Schill Et Al: Deposition and Immersion-mode Nucleatiomentioning
confidence: 72%
See 2 more Smart Citations
“…Unlike field measurements, however, it has been suggested that all volcanic ash may have similar ice nucleation efficacy, initiating ice formation in a relatively narrow temperature range of approximately 250 to 260 K (Durant et al, 2008); however, these works are difficult to interpret quantitatively, especially in cases where the nucleation mode is unclear, frozen fractions are unavailable, or the available surface area has not been quantified. More recently, several studies have investigated the deposition-and/or immersion-mode ice nucleation properties of ash from the 2010 eruption of the Eyjafjallajökull volcano in Iceland (Steinke et al, 2011;Hoyle et al, 2011;Bingemer et al, 2012). The results of these studies, combined with previous studies on large, 250-300 µm ash particles from the 1980 Mt.…”
Section: G P Schill Et Al: Deposition and Immersion-mode Nucleatiomentioning
confidence: 72%
“…It can be seen that all three ash samples exhibit minimal temperature dependence (Koop et al, 2000). Also included are onset results from depositional ice nucleation experiments on ash from the 2010 Eyjafjallajökull eruption (Hoyle et al, 2011;Steinke et al, 2011) and a parameterization for depositional ice nucleation on KGa-1b (Sihvonen et al, 2014).…”
Section: Depositional Ice Nucleation On Volcanic Ash Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each J hom data set was weighted equally by representing it with three data points, at the maximum, minimum, and average temperature, determined from a straight line fit to ln(J hom ) versus T. In addition, we grouped measurements from separate papers, but made with the same instrument and methodology, into single data sets (i.e., we grouped data from Duft and Leisner 58 with Rzesanke et al, 59 Stöckel et al 61 with Kabath et al, 62 as well as Hoyle et al 64 with Lüönd et al 65 ). The resulting CNT fits are shown in Figure 3, with different lines originating from employing different parameterizations of D(T).…”
Section: Fitting the Cnt-based Model To Experimental Datamentioning
confidence: 99%
“…1,56 In this study, we have selected a subset [56][57][58][59][60][61][62][63][64][65][66][67][68] of the available data sets for the purposes of constraining the new parameterization. The criteria for selection were (i) minimal and well defined uncertainties, (ii) good reproducibility within the data set, and (iii) an internal droplet pressure of about 1 bar.…”
Section: Fitting the Cnt-based Model To Experimental Datamentioning
confidence: 99%